(3UahI CTYGQ GdYQHs - (3eMeO Hf CHj GdNWGH GdbQTj , CHh RjO , GHf CHj GdNWGH,J (B170 (3g` s
(3ChdgG (B:s
(3NQLJ HgG CeTj JLQ hQGAfG Ydi EKQfG CPjGd eQW oeQMd s
(3BNQgG (B:s
(3hCcSH eLOkG Ch Jbhe fhGFMj Ydj Hdjd HGcjGJ hYhOj Pdc hGdMeO ddg hMOg cGf GdaQGZ ef fSGNJg s
(3ChQGbgG eVWQHI GdJQJjHs
(3HgG fXGe GdJYbjHIs
(3QhGjI CHj MGJe GdSLSJGfj Yf GdCUeYjs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs